Long-Term Trends in the Distribution of Wealth and Inheritance - James B. Davies; Rodrigo Lluberas; Daniel Waldenström (CESifo GmbH, 2024)
This paper examines long-term trends in aggregate wealth and inheritance and in their distributions, focusing on developed economies. A key stylized fact is that wealth is less equally distributed than income. Financial assets predominate among the wealthy, while owner-occupied housing is crucial for middle groups, so higher stock prices raise wealth inequality while house price increases do the opposite. Inheritances exacerbate absolute wealth inequality but reduce rel-ative inequality. Wealth inequality declined in advanced Western countries during the first half of the 20th century, then stabilized or rose. Aggregate wealth-to-income ratios have fluctuated, re-flecting both market and policy influences, whereas inherited wealth proportions have declined over the long run. Continued increases in the value of employer-based pensions, housing and social security wealth in recent decades have acted to reduce wealth inequality, offsetting the disequalizing impact of financial asset price increases to a varying extent across countries.
Keywords: E01; H55; D15; D31; E21; G51; 330; wealth; inheritance; inequality; saving; history